MEANING ANALYSIS OF ISOGU, ASERU, AND AWATERU AS A SINONIM - Rahmah, Anisaa Fadhila Ziadatu; Haristiani, Nuria (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
Synonyms are the words with different forms that means exactly or nearly same as another word. For examples, ‘isogu,’aseru’, and ‘awateru’ verbs in Japanese. These three verbs express a hasty act or state in Indonesian language. In this research, the ‘isogu’, ‘aseru’ and ‘awateru’ verbs were analyzed to find out the similarities, differences, and whether they can be substituted by one or another in a sentence. Data were obtained from various sources such as novels, dictionaries, etc. and were analyzed using descriptive analysis methods. The result of this research showed that ‘isogu’, ‘aseru’ and ‘awateru’ verbs can be simplified and translated to the word ‘terburu-buru’ in Indonesian. Nevertheless, these three verbs also have other meanings. ‘Isogu’ verb has other meanings like ‘cepat’ (fast), ‘bergegas’ (hurry), and ‘segera’ (quickly). These meanings are closely related to the speed which the actions are taken. While the verbs of ‘aseru’ and ‘awateru’ have other meanings such as ‘panik’ (panic) and ‘gugup’ (nervous), these meanings are related to the feelings.